Associations Among Maternal Positivity, Negativity and Child Attachment in the Netherlands, Poland, and Turkey - Lubiewska, Katarzyna; Sümer, Nebi; Głogowska, Karolina; Aran, Özlü; de Raad, Wouter (Frontiers in Psychology, 2022)
This study addresses how maternal positivity and negativity toward a child in three countries, separately and in combination are related to attachment in middle childhood. We first developed an ecologically valid emic measure of the Maternal Positivity-Negativity Scale through an interview-based study (90 mothers) and then tested our hypotheses in a separate study. The child’s attachment security (where the child uses the mother as a safe haven and secure base) and insecurity (attachment anxiety and avoidance) were assessed using standard measures. Equal numbers of mothers and their children between 8 and 12 years of age from Poland, Turkey, and the Netherlands participated in the main study (756 dyads). Results revealed that: (1) maternal positivity was more strongly associated, than maternal negativity, with child security; (2) maternal negativity was more strongly associated, than maternal positivity, with child anxiety, and its relation was stronger when maternal positivity was low; (3) maternal negativity was more strongly associated with child anxiety than with child avoidance; (4) the maternal positivity-over-negativity prevalence index was related to child attachment security and insecurity; (5) relations between maternal positivity and child attachment were moderated by culture. Results are discussed considering attachment in middle childhood and culture-related perspectives.